2016
DOI: 10.18632/oncotarget.12606
|View full text |Cite
|
Sign up to set email alerts
|

SENP1 promotes proliferation of clear cell renal cell carcinoma through activation of glycolysis

Abstract: Metabolic shift toward aerobic glycolysis is a fundamental element contributing to the development and progression of clear cell renal cell carcinoma (ccRCC). We and others previously observed enhanced glycolysis and diminished tricarboxylic acid (TCA) cycle activity in ccRCC tissue. Here, by integrated gene expression and metabolomic analyses of 36 matched pairs of tumor and adjacent normal tissues, we showed that expression of Sentrin/SUMO-specific protease 1 (SENP1) is positively associated with glycolysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 58 publications
0
28
0
Order By: Relevance
“…Wang et al showed that increased SENP1 level in A549 cells promoted cell proliferation, while the inhibition of SENP1 induced G1 cell cycle arrest and radiosensitivity. Dong et al also reported that the knockdown of SENPs in clear cell renal cell carcinoma (ccRCC) cells inhibited cell proliferation. They revealed that the expression of SENP1 was positively correlated with pathological grades of ccRCC tumor, and the high expression of SENP1 was an indicator of poor overall survival and advanced ccRCC tumors .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Wang et al showed that increased SENP1 level in A549 cells promoted cell proliferation, while the inhibition of SENP1 induced G1 cell cycle arrest and radiosensitivity. Dong et al also reported that the knockdown of SENPs in clear cell renal cell carcinoma (ccRCC) cells inhibited cell proliferation. They revealed that the expression of SENP1 was positively correlated with pathological grades of ccRCC tumor, and the high expression of SENP1 was an indicator of poor overall survival and advanced ccRCC tumors .…”
Section: Discussionmentioning
confidence: 99%
“…Dong et al also reported that the knockdown of SENPs in clear cell renal cell carcinoma (ccRCC) cells inhibited cell proliferation. They revealed that the expression of SENP1 was positively correlated with pathological grades of ccRCC tumor, and the high expression of SENP1 was an indicator of poor overall survival and advanced ccRCC tumors . The results in our present study were consistent with those from Wang and Dong et al, showing that SENP1 was a risk factor for the poor prognosis of patients with NSCLC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations